Evaluation of the Impact of Interdisciplinary Case-Based Courses in Dental Education on Smile Evaluation Skills of Undergraduate Students - (:unkn) unknown (AVES, 2019)
Objective: The purpose of the present study was to compare the perception of smile aesthetic between 3rd-, 4th-, and 5th-year dental students to identify if interdisciplinary courses have an impact on the attitudes of students. Methods: A total of 118 dental students (3rd-, 4th-, and 5th-year; N=43, 43, and 32, respectively) assessed the aesthetic attractiveness of four smile photographs (normal, high, low, and asymmetric smile lines). To enhance the crown, length-to-width ratio and color Digital Smile Design (DSD) were applied to all photographs, and then scoring was performed by using the Visual Analog Scale (VAS). Results: The VAS scores were all <60 regardless of the year of the student. The lowest scores were given for asymmetric smile line. Comparison of the scores of the different years showed statistically insignificant scores between 3rd- and 4th- year dental students (p>0.05), whereas statistical differences between 4th- and 5th-year dental students were found (Cases 1, 2, and 3:p<0.05 and Case 4: p<0.01). Conclusion: All students were critical in the evaluation of smiles. Hence, the motivation for critical thinking based on multidisciplinary courses until 3rd year, the skepticism, and also the perception of the students were increased. The difference between 4th- and 5th-year student aesthetic perceptions showed the impact of interdisciplinary course on enhanced judgment competency of the students.
Keywords: Case-based learning; interprofessional education; undergraduate orthodontic education; AESTHETICS; PROFESSIONALS; PERCEPTIONS; LAYPERSONS